Pelatihan Pembuatan Sirup Kalamansi Sebagai Produk Unggulan Provinsi Bengkulu di Kelurahan Lempuing Kota Bengkulu - Hestiawan, Hendri; Suryadi, Dedi; Afrizal, Yuzuar; Fadilah, M. Hafidz (Dharmakayana, 2025)
Kalamansi oranges (Citrus microcarpa) are a horticultural commodity typical of Bengkulu Province with high economic potential. However, their utilization as a value-added processed product is still limited. This training activity aims to provide knowledge and skills in making kalamansi syrup, a superior product of Bengkulu Province, to residents of RT 18, Lempuing Village, Bengkulu City. The activity was carried out through socialization, practice, and evaluation methods. The training results showed an increase in participants' knowledge and skills and the formation of a small-scale business development plan. This activity supports community empowerment and strengthening the local economy, while promoting Bengkulu's signature products.